Characteristics of Brazilian school food and physical activity environments: PeNSE 2015 - Lucyane Barbosa Oliveira Souza; Ana Beatriz Coelho de Azevedo; Daniel Henrique Bandoni; Daniela Silva Canella (Universidade de São Paulo, 2022)
ABSTRACT OBJECTIVE To characterize the food and physical activity environments in Brazilian public and private schools, and develop indicators to evaluate them. METHODS This is a cross-sectional study conducted with data from a questionnaire on school characteristics of the 2015 National Adolescent School-based Health Survey, answered by principals or coordinators, referring to 3040 public and private schools throughout the country. The variables related to food and physical activity environments were described in isolation, and an indicator was developed for each environment, with scores ranging from 0 to 100. The frequency and mean score of each variable were described according to the administrative sphere (public or private). RESULTS The public sector showed a predominance of school meals offer (97.8%), whereas the private sector, of canteens (89.8%). Both had a similar frequency of alternative food outlets in the surroundings. Private schools provided all markers of healthy and unhealthy eating in canteens more frequently. Public schools scored higher in "Food and beverage availability" (64.9) than private schools (55.8). The characteristics of physical activity environments showed that sports courts and sports or games equipment were common in public (69.2% and 90.7%, respectively) and private schools (94.1% and 99.8%, respectively), though at a significantly higher frequency in the second group. Private schools scored higher in "Structures and materials availability" than public schools (63.3 and 41.6, respectively). CONCLUSIONS Public schools provide a more favorable food environment, whereas private schools, a physical activity environment.